Anesthetic management of abdominal delivery in females with multiple pregnancy - N. V. Mamovich; S. V. Kinzhalova; R. A. Makarov; R. T. Shakirov (Вестник анестезиологии и реаниматологии, 2019)
The article analyzes domestic and foreign publications from 2009 to 2019, found in the MEDLINE, PubMed, Embase, Web of Science database on the topic: multiple pregnancy, complications, outcomes, and anesthesia for cesarean section. The data on the prevalence, complications and outcomes of multiple pregnancies are presented. Optimal timing and methods of delivery for multiple pregnancy, their influence on perinatal outcomes have been determined. The review examines different methods of anesthesia and their influence on the mother, the intrauterine condition of the fetus and newborn undergoing a cesarean section. Currently, the main methods of anesthesia for cesarean section are regional ones. Among the methods of neuroaxial anesthesia, spinal anesthesia is preferred. Given the limited data on the impact of regional anesthesia methods on the mother and fetus/fetus during multiple pregnancies, additional research is needed.